Efektivitas Pelatihan Asertivitas dalam Mengurangi Perilaku Bullying terhadap Tunanetra di SMK Negeri 7 Padang - Putri, Vidia Nurul Rada; Marlina, Marlina (Jurnal Penelitian Pendidikan Khusus, 2022)
In an effort to reduce bullying, assertiveness training was carried out in this study. This research is an experiment with Single Subject Research approach with A1-B-A2 design. Implemented for visual impairment students who experience bullying at SMK N 7 Padang with data collection techniques is direct observation and interview. Data were analyzed using visual ghraphic. Based on the data analysis that has been done, it can be explained that after being given assertiveness training, bullying behavior towards visual impairment students has decreased. So that assertiveness training has an effect on reducing bullying behavior towards visual impairment children at SMK N 7 Padang.